A POLÍTICA CULTURAL NA REVOLUÇÃO CUBANA: as disputas intelectuais nos anos 1960 e 1970 - Cezar Miskulin, Sílvia (Caderno CRH, 2019)
A Revolução Cubana promoveu grandes transformações na sociedade da ilha. Novas publicações, instituições culturais e manifestações artísticas acompanharam a efervescência política e cultural ao longo dos anos 60. Esta pesquisa analisou o suplemento cultural Lunes de Revolución, a editora El Puente e o suplemento cultural El Caimán Barbudo, com o objetivo de mostrar o surgimento das novas publicações e manifestações culturais em Cuba após o triunfo da Revolução. O trabalho demonstra que o surgimento de uma política cultural acarretou a normatização e o controle das produções culturais pelo governo cubano desde os anos 1960, e mais ainda após 1971, quando se acentuou o fechamento e o endurecimento no meio cultural cubano. CULTURAL POLICY IN THE CUBAN REVOLUTION: intellectual disputes in the 1960s and 1970s The Cuban Revolution promoted great transformations in the society of the island. New publications, cultural institutions and artistic manifestations accompanied the political and cultural effervescence throughout the 1960s.This research analyzed the cultural supplement Lunes de Revolución, the El Puente publishing house and the El Caimán Barbudo cultural supplement, with the aim of showing the emergence of new publications and cultural manifestations in Cuba after the triumph of the Revolution. However, the emergence of a cultural policy has led to the normalization and control of cultural productions by the Cuban government since the 1960s, and especially after 1971, when the closing and hardening of the Cuban cultural milieu became more pronounced. Key words: Cuba. Revolution. Culture. History. Intellectual. LA POLITIQUE CULTURELLE DANS LA REVOLUTION CUBAINE: controverses intellectuelles dans les annees 1960 et 1970 La révolution cubaine a promu de grandes transformations dans la société de l’île. De nouvelles publications, des institutions culturelles et des manifestations artistiques ont accompagné l’effervescence politique et culturelle tout au long des années 1960.Cette recherche a analysé le supplément culturel Lunes de Revolución, la maison d’édition El Puente et le supplément culturel El Caimán Barbudo, dans le but de montrer l’émergence de nouvelles publications et manifestations culturelles à Cuba après le triomphe de la Révolution. Cependant, l’émergence d’une politique culturelle a conduit à la normalisation et au contrôle des productions culturelles par le gouvernement cubain depuis les années 1960, et encore plus après 1971, lorsque la fermeture et l’endurcissement du milieu culturel cubain se sont accentués. Mots clés: Cuba. Révolution. Culture. Histoire. Intellectuel.